2014
DOI: 10.1159/000358232
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Alzheimer's Disease in Two Iranian Families: A Genetic Study

Abstract: Background: Early-onset Alzheimer's disease (EOAD) represents less than 5% of all AD cases. Autosomal dominant EOAD has been defined as the occurrence of at least three cases in three generations. Mutations in the amyloid precursor protein (APP), presenilin-1 and presenilin-2 genes have been recognized to be the cause of EOAD. Objective: We investigated the genotype of EOAD in two generations of two families with EOAD living in an Iranian village. Methods: The polymerase chain reaction method was used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Myoclonic seizures, which are usually reported in about 47% of the cases with PSEN1 mutations with 23% of the patients presenting them in the advanced stages of the disease (Ryan et al, 2016), were also developed in all patients from Family 2. Although an APP mutation was previously reported in Iranian AD subjects (Noroozian et al, 2014), this study represents the first report of PSEN1 genetic variability in the Iranian population. The identified PSEN1 p.Gly206Asp mutation has been previously reported as a causal mutation in ADAD patients of various origins (Dobricic et al, 2012; Raux et al, 2005; Rogaeva et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…Myoclonic seizures, which are usually reported in about 47% of the cases with PSEN1 mutations with 23% of the patients presenting them in the advanced stages of the disease (Ryan et al, 2016), were also developed in all patients from Family 2. Although an APP mutation was previously reported in Iranian AD subjects (Noroozian et al, 2014), this study represents the first report of PSEN1 genetic variability in the Iranian population. The identified PSEN1 p.Gly206Asp mutation has been previously reported as a causal mutation in ADAD patients of various origins (Dobricic et al, 2012; Raux et al, 2005; Rogaeva et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…Early-onset AD typically affects people younger than 65 years old. Early-onset, known as familial, constitutes roughly 5% of AD cases with patients as young as their 40s, and symptoms may start to develop between 30 and 40 [ 4 , 5 ]. In contrast, late-onset AD strikes 65 years and above and ultimately represents the larger proportion of AD cases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have shown that gout has an association with cancers (Boffetta et al, 2009;Kuo et al, 2012), especially kidney cancer bladder cancer, and prostate cancer (Loeb and Harris, 2008;Chen, 2014). Well-known risk factors for both gout and cancer may include obesity, hyperglycemia, heavy alcohol use as well as inflammation syndrome (Bianchini et al, 2002;Aggarwal and Gehlot, 2009;Greer and Whitcomb, 2009;Noroozian et al, 2014). In particular, inflammation has been well documented to be related to several cancers (Coussens and Werb, 2002;Balkwill and Coussens, 2004), including colorectal cancer (McMillan et al, 2003), pancreatic cancer (Jamieson et al, 2005;Greer and Whitcomb, 2009), urinary bladder cancer (Hilmy et al, 2005), and renal clear cell cancer (Lamb et al, 2006).…”
Section: Introductionmentioning
confidence: 99%